Bahasa Inggeris - KHAIRUL NIZAM BIN ZAINAL BADRI (SEUNEUBOK LADA: Jurnal ilmu-ilmu Sejarah, Sosial, Budaya dan Kependidikan, 2021)
History has recorded the glory of Aceh in the culture of intellectual philosophy in the 16th century through the manuscripts which have been produced by scholars at the figures of the era. But to be fair, research should take into account the contributions of sponsors, or motivators to such activities. So of course the biggest contributor to the journey to restore the intellectual tradition lies in the hands of the government. In the context of the implementation of the initiators of scientific activities, the name of Sultan Alaudin Mansur Shah, ruler of Aceh's 8th; should be on the radar of researchers. Therefore, this study sought to examine the philosophy of science and its significance to the development of Aceh during the reign of Sultan Alaudin Mansur Shah. Using literature review and social cognitive theory approach, this paper seeks to trace one by one the data related to the advancement of the philosophy of science at that time. The philosophy of knowledge turns out to make a great contribution to a precise understanding in the field of religion; and most important is the awareness to bear the trust, as the caliph on this earth.